Usefulness of a Cannula with a Flexible Tip (Swing Tip) for Managing Severe Biliary Stricture - Daisuke Uchida; Hironari Kato; Yosuke Saragai; Saimon Takada; Shinichiro Muro; Takeshi Tomoda; Kazuyuki Matsumoto; Shigeru Horiguchi; Hiroyuki Okada (Canadian Journal of Gastroenterology and Hepatology)
Background and Aims. Biliary stenting for the treatment of biliary stricture is the most common indication of ERCP, but the procedure is sometimes unsuccessful because of severe strictures. The Swing Tip is useful for passing through severe strictures because it has a manually operable tip. The efficacy of using a Swing Tip was retrospectively evaluated. Methods. The 2353 patients who underwent ERCP for biliary stenting at our facility between January 2012 and July 2018 were enrolled. In all patients, procedures were begun using tapered tip-catheters, and Swing Tips were used if the procedure was found to be difficult with other devices. The indication for switching to the Swing Tip and the technical success rate were retrospectively evaluated. Results. A total of 99 patients (4.2%) underwent ERCP using the Swing Tip, including 49 patients for the selection of biliary branches and 50 for exchanging guidewires for rigid ones. In these patients, biliary stenting was successful in 22 patients (44.9%) and 45 patients (90%), respectively. The other 32 patients with failed endoscopic biliary drainage were treated via alternative approaches, such as percutaneous procedures, surgeries, or conservative treatments. There were no adverse events associated with the Swing Tip. Conclusion. The Swing Tip was technically feasible especially for exchanging guidewires during ERCP. Percutaneous procedures or surgical treatments can be avoided by using the Swing Tip. Ethical Statements. This study was approved by the institutional review board of Okayama University. All subjects provided informed consent. The study was registered in the UMIN protocol registration system (identification number UMIN 000033692).